Metformin Hydrochloride Significantly Inhibits Rotavirus Infection in Caco2 Cell Line, Intestinal Organoids, and Mice - Rui Zhang; Cui Feng; Dandan Luo; Ruibo Zhao; Perumal Ramesh Kannan; Yuebang Yin; Muhammad Zubair Iqbal; Yeting Hu; Xiangdong Kong (MDPI AG, 2023)
Rotavirus is one of the main pathogens that causes severe diarrhea in children under the age of 5, primarily infecting the enterocytes of the small intestine. Currently, there are no specific drugs available for oral rehydration and antiviral therapy targeting rotavirus. However, metformin hydrochloride, a drug known for its antiviral properties, shows promise as it accumulates in the small intestine and modulates the intestinal microbiota. Therefore, we formulated a hypothesis that metformin hydrochloride could inhibit rotavirus replication in the intestine. To validate the anti-rotavirus effect of metformin hydrochloride, we conducted infection experiments using different models, ranging from in vitro cells and organoids to small intestines in vivo. The findings indicate that a concentration of 0.5 mM metformin hydrochloride significantly inhibits the expression of rotavirus mRNA and protein in Caco-2 cells, small intestinal organoids, and suckling mice models. Rotavirus infections lead to noticeable pathological changes, but treatment with metformin has been observed to mitigate the lesions caused by rotavirus infection in the treated group. Our study establishes that metformin hydrochloride can inhibit rotavirus replication, while also affirming the reliability of organoids as a virus model for in vitro research.